Active small bowel sparing in intracavitary brachytherapy for cervical cancer. (27th December 2021) - Goh, Youngmoon; Kim, Dohyeon; Kim, Joo-Young; Kim, Hak Soo; Jeong, Jong Hwi; Lee, Sung Uk; Youn, Sang Hee; Oh, Eun Sang; Ha, Bo Ram; Yeo, Adam Unjin; Kim, Myeongsoo; Shin, Dongho; et al.
Abstract: Objective: To propose and evaluate an active method for sparing the small bowel in the treatment field of cervical cancer brachytherapy by prone position procedure. Methods: The prone position procedure consists of five steps: making bladder empty, prone-positioning a patient on belly board, making the small bowel move to abdomen, filling the bladder with Foley catheter and finally turning the patient into the supine position. The proposed method was applied for the treatment of seven cervical cancer patients. Its effectiveness was evaluated and a correlation between the patient characteristics and the volumetric dose reduction of small bowel was also investigated. Brachytherapy treatment plans were built before and after the proposed method, and their dose-volume histograms were compared for targets and organs-at-risk. In this comparison, all plans were normalized to satisfy the same D 90% for high-risk clinical target volume. Results: For the enrolled patients, the average dose of small bowel was significantly reduced from 75.2 ± 4.9 Gy before to 60.2 ± 4.0 Gy after the prone position procedure, while minor dosimetric changes were observed in rectum, sigmoid and bladder. The linear correlation to body mass index, thickness and width of abdominopelvic cavity and bladder volume were 76.2, 69.7, 28.8 and −36.3%, respectively. Conclusions: The application of prone position procedure could effectively lower the volumetric dose of the small bowel. The dose reduction in the small bowel had a strong correlation with the patient's obesity and abdominal thickness. This means the patients for whom the proposed method would be beneficial can be judiciously selected for safe brachytherapy. Abstract : We proposed a novel method to reduce the volumetric dose of small bowel in intracavitary brachytherapy, evaluated its effectiveness for cervical cancer patients and finally suggested the patient selection criteria.